CYBERCRIME IN THE CONDITIONS OF THE DIGITAL ECONOMY AND THE NEW TENDENCIES IN THE FORENSIC ENQUIRY DEVELOPMENT - Klimovich L. Р.; Molokov V. V. (Scientific Journal of Pedagogy and Economics, 2019)
. The rationale of the article is contingent on the possible security threats afflicting the digital economy in the context of the cybercrime spreading. The authors emphasize the important role of the law enforcement agencies in the prevention and suppression of computer crimes, determine their priority tasks and propose the possible solutions to them. The research content touches upon the topical issues of the computer forensic analysis in the conditions of the digital economy development in the Russian Federation. The study focuses on the experts’ tasks, problems of implementation and demand for various types of the computer forensics, taking into account the tendencies of the criminal attacks on information and telecommunication systems and the equipment. The article justifies the importance of conducting the comprehensive computer forensics in order to obtain the forensically relevant information when investigating crimes committed using the Internet. From the standpoint of the economy digitalization development analysis, the authors offer the options for the forensics practice improvement and organization of the training for the experts in the forensic units. From the standpoint of the economy digitalization development analysis, the authors suggest the solutions for the computer forensics practice improvement and organization of the training for the experts in the forensic units.